Improve Algoritma Hodgson Untuk Meminimasi Jumlah Job Terlambat Pada Penjadwalan Flow shop - Dian Setiya Widodo (Jurnal Teknik Industri, 2018)
Since Johnson published a paper in 1954, the problem of job scheduling has received the attention of hundreds of practitioners and researchers, as one of the most studied topics in Operation research. Several heuristic studies have discussed the problem of flow shop scheduling to minimize the completion time (makespan). In this paper, we consider the problem of pure flow shop scheduling to minimize the number of jobs of tardy. We have developed a Hudson algorithm for minimization solution the number jobs of tardy. Hodgson's improved Heuristic algorithm was tested and compared to the EDD priority rule. The Numerical experimental results show the new algorithm provides a better solution than priority EDD. The improving Hodgson algorithm gives a minimum number of tardy jobs.